2009
DOI: 10.1080/10409230903061215
|View full text |Cite
|
Sign up to set email alerts
|

Gap junctional intercellular communication as a target for liver toxicity and carcinogenicity

Abstract: Direct communication between hepatocytes, mediated by gap junctions, constitutes a major regulatory platform in the control of liver homeostasis, ranging from hepatocellular proliferation to hepatocyte cell death. Inherent to this pivotal task, gap junction functionality is frequently disrupted upon impairment of the homeostatic balance, as occurs during liver toxicity and carcinogenicity. In the present paper, the deleterious effects of a number of chemical and biological toxic compounds on hepatic gap juncti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
87
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(90 citation statements)
references
References 281 publications
3
87
0
Order By: Relevance
“…158,159 Other studies reported that the deleterious spermatogenic effect coupling and degradation. 27,167 Since most of the mitogen-activated protein kinase signaling pathways, which mediate the toxicant-induced hepatic 139 and testicular 126 injury, also control Cx43 phosphorylation, it is likely that toxicants, through these signaling pathways, affect Cx phosphorylation and consequently the role of Cx43 gap junctions between Sertoli cells and between Sertoli and germ cells. In agreement with this hypothesis, our laboratory demonstrated that many environmental toxicants (DDT, pentachlorophenol, dieldrin, dinitrobenzene, cadmium chloride, cisplatin, gossypol, bisphenol A and tert octylphenol) disrupt GJIC by reducing the amount of Cx43 and inducing aberrant intracellular localization of the protein in immature Sertoli cells.…”
Section: Effects Of Environmental Toxicants On Connexin 43 In the Devmentioning
confidence: 99%
See 1 more Smart Citation
“…158,159 Other studies reported that the deleterious spermatogenic effect coupling and degradation. 27,167 Since most of the mitogen-activated protein kinase signaling pathways, which mediate the toxicant-induced hepatic 139 and testicular 126 injury, also control Cx43 phosphorylation, it is likely that toxicants, through these signaling pathways, affect Cx phosphorylation and consequently the role of Cx43 gap junctions between Sertoli cells and between Sertoli and germ cells. In agreement with this hypothesis, our laboratory demonstrated that many environmental toxicants (DDT, pentachlorophenol, dieldrin, dinitrobenzene, cadmium chloride, cisplatin, gossypol, bisphenol A and tert octylphenol) disrupt GJIC by reducing the amount of Cx43 and inducing aberrant intracellular localization of the protein in immature Sertoli cells.…”
Section: Effects Of Environmental Toxicants On Connexin 43 In the Devmentioning
confidence: 99%
“…It is well established that gap junctions and Cxs are potential targets for many environmental compounds that could exhibit cell type/ tissue/organ specificities and induce distinct pathological consequences (embryo lethality and neurotoxicity of the central nervous system, skin hyperplasia, teratogenesis and reproductive dysfunction). 16 Generally, the adverse effects of these chemical compounds on Cx can occur at the transcriptional, translational and posttranslational levels 138 and may affect many organs such as liver 139 and testis. 17 The result of environmental toxicants on male reproductive function, specifically mediated through Cx alteration, could be a consequence of effects that occur at several levels: hypothalamus/pituitary, thyroid, testis (Fig.…”
Section: Connexin Expression Function and Regulation In The Developimentioning
confidence: 99%
“…Gap junctions play key roles as goalkeepers in virtually all aspects of tissue homeostasis, including cell growth, cellular differentiation and cell death. Inherent to this pivotal function, it is not surprising that they are frequently involved in situations where tissue function is compromised (Vinken et al, 2009b(Vinken et al, , 2008. This manuscript reviews the modifi cation of connexin production in liver development.…”
Section: Introductionmentioning
confidence: 99%
“…Gap junctions are composed of two hemichannels of neighbouring cells, which in turn are built up by six transmembrane connexin (Cx) proteins (Figure 1). More than 20 connexin paralogues have been characterised in human and rodents, all which are expressed in a cell type-specifi c manner and are named according to their molecular weight (Decrock et al, 2009;Vinken et al, 2006aVinken et al, , 2006bVinken et al, , 2009aVinken et al, , 2009bVinken et al, , 2008Vinken et al, , 2011. Gap junctions play key roles as goalkeepers in virtually all aspects of tissue homeostasis, including cell growth, cellular differentiation and cell death.…”
Section: Introductionmentioning
confidence: 99%
“…Different contributions in this Special Issue particularly by C. Distelhorst and M. Bootman, and by N. Prevarskaya and colleagues, deal with different aspects of cell death in cancer pathology. Cell death is not restricted to one cell, but intercellular junctions mediate spreading of cell death to neighboring cells, a mechanism that could be very important in targeting cancer cells as is further discussed in a contribution by L. Leybaert and colleagues [60,61]. Exaggerated or inappropriate cell death consistently leads to severe pathologies including particularly neurodegenerative diseases [62] and normal aging [63,64].…”
Section: Camentioning
confidence: 99%